A Newly Discovered Anthropomorphic Vessel from Eastern Bulgaria - Danov, Veselin (Archaeologia Lituana, 2022)
The topic of prehistoric anthropomorphic sculpture, its presentation and interpretation are widely covered in the works of Marija Gimbutas. In her honor is the submitted paper, which presents a representative and very interesting vessel. It is a vessel in the shape of a human body, rare in the Eneolithic era. The vessel was found accidentally on the surface of a settlement mound. It is partially preserved, but the available fragments allow to restore its shape and ornamentation. The massive legs and long feet allow the vessel to be placed upright. It is one of the most impressive specimens among this type of finds which represents a female mythological image, probably the Mother Goddess. Specific shape and ornamentation of the vessel suggest representative functions, probably used in various rites associated with prayers for fertility.